The contribution of online multimodal feedback-based weblogs toward students writing skills enhancement - Asnawi Muslem; Saiful Marhaban; Sofyan A Gani; Siti Hamdalah; Dina Amalia; Emma Hankinson (Studies in English Language and Education, 2024)
Writing correctly and accurately in English is essential for communicating formally with others in this 4.0 era. Various approaches, methods, techniques, strategies, and media have been used to improve students writing skills. However, students still require help with writing correctly and accurately in English. This study aims to investigate whether online multimodal feedback-based weblogs improve students writing skills and to discover the students perceptions of using this teaching model. Fifty students were included in this quasi-experimental study. They were divided into two groups: experimental and control groups, with 25 students in each group. The experimental group was taught writing with online multimodal feedback-based weblogs, and the control group was taught writing using the traditional method. A written test was used to collect data in both pre-test and post-test. A set of questionnaires was also used to collect information about the students perceptions of the teaching model used. The research results showed that online multimodal feedback-based weblogs could improve the students writing skills. Furthermore, students in the experimental group positively responded to the use of online multimodal feedback-based weblogs in teaching and learning writing. Hence, it can be inferred that weblogs incorporating online multimodal feedback have the potential to enhance both the writing proficiency and motivation of students.